Pengaruh Penggunaan Model STAD Terhadap Minat Belajar Peserta Didik Pada Pembelajaran Sejarah Kelas XI SMA Negeri 1 Toho - Portunata, Antonia Sri Dwi; Aminuyati, Aminuyati; Putri, Astrini Eka (Peneliti.net, 2025)
Many issues arise during teaching, particularly when it comes to teaching history. One issue that frequently arises in the classroom is that professors are more involved than students are, which makes the learning process passive. In addition, some students believe that studying history is not a subject they should be studying. Less engaging as history is required to be memorized by students, which makes history instruction unpopular and, in turn, makes students less interested in studying history. Students who receive content that infrequently use a variety of learning approaches get disinterested in studying history. This calls for the use of an appropriate learning model, such as the STAD model. Quantitative techniques with a quasi-experimental design are used in this study. Questionnaires, documentation, and observation techniques are the approaches utilized to collect data. Research instrument analysis, prerequisite data analysis, and hypothesis data test procedures are the data analysis approaches that are employed. According to the findings, the average score for the STAD model's application in class XI IPS3 was 94.58, placing it in the very good category. Additionally, the model's impact on history learning was shown to be statistically significant at (1.671) > (1.058). These findings showed that Ha was accepted and Ho was denied. The STAD model's influence on students' interest in learning history is 0.743, or 0.5 ≤ d ≥ 0.8, in terms of size. This indicates that the model's application has a noteworthy but relatively modest impact on students' interest in learning history.